Evaluation of corticospinal axon loss by fluorescent dye tracing in mice with experimental autoimmune encephalomyelitis - Liu, Zhongwu (2007)
In both multiple sclerosis (MS) patients and experimental autoimmune encephalomyelitis (EAE) animals, axon loss has been demonstrated to correlate with neurological disability. However, it is difficult to accurately determine the location and severity of axonal damage since the lesion in MS or EAE is disseminated and is frequently in a relapsing-remitting mode. The corticospinal system is the only direct pathway from the motorsensory cortex to the spinal cord, and the major neural pathway for control of voluntary movement. Moreover, it is frequently involved in the pathological process of the disease. To evaluate corticospinal tract (CST) axon loss in EAE mice, we developed a direct tracing method with a fluorescent neuronal tracer DiI which was injected into the primary motor cortex and sensorimotor cortex to label the pyramidal neurons. The lesion location in the spinal cord and axon disruption were indicated by dye leakage. Using the EAE induced axon reduction as an index of the extent of axonal damage, our data showed a high correlation between the axonal loss and the behavioral outcome score in the EAE mice. The results were consistent with the axonal Bielschowsky silver staining. Thus, this CST tracing method permits monitoring of the axonal damage in EAE.